Myelodysplastic Syndrome and Autoimmunity: A Case Report of an Unusual Presentation of Myelodysplastic Syndrome - Andrea L. Merrill; Hedy Smith (Case Reports in Hematology)
Myelodysplastic syndrome (MDS) commonly presents asymptomatically or with symptomatic cytopenias. However, autoimmune phenomena in association with MDS have been well described in several case reports and case series. Typically, these autoimmune phenomena take the form of vasculitides, arthritis, connective tissue diseases, pulmonary infiltrates, or polymyalgia rheumatica. We present the case of a woman with MDS (karyotype 46,XX,+1,der(1;7)(q10;p10)[20], that evolved with an additional trisomy 8 clone) and a novel spectrum of autoimmune diseases including acute fibrinous and organizing pneumonia (AFOP) and lacrimal gland pseudotumor.